Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Jdifhifnfjdjdjsjdjhdudhrudbdjdbdjxhdhdhfhdhfhfh

Jdifhifnfjdjdjsjdjhdudhrudbdjdbdjxhdhdhfhdhfhfh class=

Sagot :

Answer:

[tex](X+10)^2 = 106[/tex]

Step-by-step explanation:

To convert the quadratic equation [tex]X^2+20x-6=0[/tex] into the form [tex](x-p)^2=q[/tex], we need to complete the square. Let's go through this step-by-step:

First, let's start with our equation:

[tex]X^2+20x-6=0[/tex]

Move the constant term to the right side of the equation:

[tex]X^2+20x = 6[/tex]

To complete the square, we take half of the coefficient of x, square it, and add and subtract it from both sides:

Half of 20 is 10, and [tex]10^2 = 100[/tex]

[tex]X^2+20x+100 = 6+100[/tex]

Simplify the right side:

[tex]X^2+20x+100 = 106[/tex]

The left side is now a perfect square trinomial:

[tex](X+10)^2 = 106[/tex]

This is almost in[tex](x-p)^2=q[/tex] form. We just need to adjust it slightly:

[tex](X-(-10))^2 = 106[/tex]

Therefore, in [tex](x-p)^2=q[/tex] form, the equation [tex]X^2+20x-6=0[/tex] becomes:

[tex](X+10)^2 = 106[/tex]

Where [tex]p = -10[/tex]  and [tex]q = 106[/tex]